POLITICAL HISTORY IN 18th CENTURY OF GULLIVER’S TRAVELS BY JONATHAN SWIFT - Neisya, Neisya (Jurnal Ilmiah Bina Bahasa, 2018)
This study objectives were to find out the influence of the England political history and how Swift used the symbol of satire to criticize political situation. Qualitative method with descriptive approach was used in this study. Techniques for collecting the data were done through following: reading and observing the novel of Gulliver?s Travels, scanning and finding the information of some history of English Literature books and history books, and looking for the information related to the study of the literary theory books to get theories and references as supporting research in this study. M.H. Abrams Theory was used in finding and analyzing this study. The result of the study showed that satire was used by Swift to criticize political and social situation. It was reflected in the story of Gulliver?s Travels. For example, Swift criticize the British government by using the Lilliputians.